Sustainable materials for bioclimatic design in Dayak traditional longhouse / Janet Victoria Stia and Siti Akhtar Mahayuddin - Stia, Janet Victoria; Mahayuddin, Siti Akhtar (2019)
Traditional longhouse is a heritage dwelling of the Dayak people in Sarawak Malaysia. Traditional longhouse is unique in term of layout design with apartments of the families in the longhouse stacked side by side under one roof. In front of the row of apartments is an open common space for social activities. Basically, traditional longhouse is built from sustainable local materials such as timber, bamboo, palm tree, palm leaves and rattan. The local materials are environmentally friendly and act as the passive elements that supported the bioclimatic design of the longhouse. In this study, 15 Dayak traditional longhouses in Sarawak were surveyed for the presence of local sustainable materials. Condition survey had been conducted to these longhouses. This study found that, timber has the highest potential to be conserved as compared to bamboo, palm tree, palm leaves and rattan. The situation might due to preferences of longhouse dwellers on modern materials such as bricks, concrete, metal roofing and processed timber products such as plywood which are widely available in the market. Action need to be taken by related bodies and authorities in order to conserve the longhouse with the traditional materials.